The Italian Criminal Court of Padova sentenced the circus’ director for cruelty to animals - Carla Campanaro (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
On July 13th, 2016 the Italian Criminal Court of Padova issued an eight-month sentence to the director of the Medrano Circus for cruelty to animals as per article 544 ter of the Italian Penal Code.